Marital Satisfaction of Portuguese Families in Times of Social Lockdown - Fernandes, Carla Sílvia; Magalhães, Bruno; Silva, Sílvia; Edra, Beatriz (SAGE Journals, 2021)
Abstract The COVID-19 pandemic represents a global threat and crisis situation, and its wide-reaching impact has also affected marital satisfaction. Dysfunction of the marital system puts the survival of the family unit at risk. This research aimed to determine the level of marital satisfaction of Portuguese families during the social lockdown and the association between the variables under study. A descriptive, exploratory study was conducted. During the social lockdown, 276 people of Portuguese nationality and residing in Portugal were recruited using nonprobabilistic convenience sampling. Marital satisfaction in the pandemic phase showed low values that may be associated with the social, economic, and political context experienced by the pandemic situation. Future research must be carried out in order to identify, prevent, and intervene in situations of violence. In addition, future research should explore not only marital satisfaction during the current pandemic but a more systemic assessment of marital relations during crises, expanding the impact of marital satisfaction in family functioning.
Keywords: Family; Pandemics; Conjugal status